Gastronomy in weekly Press supplements - Turón-Padial, María-Concepción (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Gastronomy and the Press are in fashion in the 21st century. We consider that the feeding theme in the printed media has always had an informative attention as it is a business field that, at the same time, reported advertising content. Let us not forget that the reality of the so-called “mass media” worldwide is based on the Advertising. We offer an analysis of the journalistic treatment of the gastronomic field in weekly press supplements in Spain, through the most representative ones, having selected those with the greatest impact. Tables depict the data within the rigor and systematic scientific planning.